STEM-Based Microgreen Learning Media to Enhance Senior High School Students’ Science Process Skills - Lidya Vriska Fatimah Azzahra; Endang Susantini; Nensy Eka Selviana; Husfina Lailiyatus Suaidah; Muhammad Shukri (Yayasan Nurul Yakin Bunga Tanjung, 2026)
Science process skills are crucial in biology education and benefit from experiential, inquiry-based approaches. However, biology learning often remains abstract and lacks subject-specific media. This study investigated the effectiveness of STEM-based learning using biodegradable microgreen seed paper to enhance eleventh-grade students’ science process skills and learning responses in plant growth and development. Using a one-group pretest–posttest design (n = 36), students engaged in scientific inquiry, engineering-based design of seed paper, and technology-assisted observation. Science process skills were assessed via essays, and student responses via a Guttman-scale questionnaire. Data analysis with N-gain and the Wilcoxon test showed significant improvement in science process skills (pretest mean = 63.19, posttest mean = 89.03, N-gain = 0.71, Z = −5.248, p < 0.05) and very positive student responses (97%). These findings suggest STEM-based microgreen seed paper learning effectively enhances science process skills and engagement, supporting SDG 4 (Quality Education) and SDG 12 (Responsible Consumption and Production).